Nanopore Sequencing and De Novo Assembly of a Black-Shelled Pacific Oyster (Crassostrea gigas) Genome - Wang, Xiaotong; Xu, Wenjie; Wei, Lei; Zhu, Chenglong; He, Cheng; Song, Hongce; Cai, Zhongqiang; Yu, Wenchao; Jiang, Qiuyun; Li, Lingling; Wang, Kun; Feng, Chenguang (Frontiers in Genetics, 2019)
The Pacific oyster, Crassostrea gigas, belongs to one of the most species-rich phyla and provides important ecological and economical services. Here we present a genome assembly for a variety of this species, black-shelled Pacific oyster, using a combination of 61.8 Gb Nanopore long reads and 105.6 Gb raw BGI-seq short reads. The genome assembly comprised 3,676 contigs, with a total length of 587 Mb and a contig N50 of 581 kb. Annotation of the genome assembly identified 283 Mb (48.32%) of repetitive sequences and a total of 26,811 protein-coding genes. A long-term transposable element active, accompanied by recent expansion (1 million years ago), was detected in this genome. The divergence between black-shelled and the previous published Pacific oysters was estimated at about 2.2 million years ago, which implies that species C. gigas had great intraspecific genetic variations. Moreover, we identified 148/188 specifically expanded/contracted gene families in this genome. We believe this genome assembly will be a valuable resource for understanding the genetic breeding, conservation, and evolution of oysters and bivalves.